Respuestas

  • Usuario de Brainly
2013-08-24T21:12:03+02:00
a²  - 1           :   2a - 2a²
3a² + a - 2            4

Primero factorizas
a² - 1 = (a -1)(a +1)    Diferencia de cuadrados
2a - 2a² = -2a ( - 1 +  a )  Factor común
3a² + a - 2 = Trinomio Cuadrado no Perfecto →(a - 2/3)(a +1)
3a² + a - 2 = (a - 2/3)(a +1)

ahora reemplazas
a²  - 1           :   2a - 2a²
3a² + a - 2            4

(a -1)(a +1)        :  - 2a (a -1 ) 
 (a - 2/3)(a +1)         4

ahora simplificamos
(a -1) con (a-1)  y (a +1)con (a+1) nos queda

         1       :  - 2a      
 (a - 2/3)              4 

ahora resolvemos
       4            
 (a - 2/3)(-2a)          

espero que te sirva, salu2!!!!!